2017
DOI: 10.1021/acschembio.6b00913
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Focused Screening with Biological Fingerprints Identifies Selective Asc-1 Inhibitors Distinct from Traditional High Throughput Screening

Abstract: Kutchukian, P. S. et al. (2017) Iterative focused screening with biological fingerprints identifies selective Asc-1 inhibitors distinct from traditional high throughput screening. ACS Chemical Biology, 12(2), pp. 519-527. (doi:10.1021/acschembio.6b00913) This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/146530/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…We then used this model to select high-scoring molecules from our company’s compound collection for subsequent screening against the RNA targets. By including multiple expansion methods, additional chemotypes can be discovered; 27 thus, we also included compounds that were nearest neighbors based on chemical or biological similarity to the RNA binders. Comparison of the resulting set of ~3700 compounds, termed the “RNA-Focused Library,” with reference to the initial screening collection using Tanimoto similarity, revealed that our new set included similar compounds (high similarity) as well as distinct chemical moieties (low similarity), the latter largely introduced through biological fingerprint nearest-neighbor expansion and ECFP4 naïve Bayesian model expansion ( Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…We then used this model to select high-scoring molecules from our company’s compound collection for subsequent screening against the RNA targets. By including multiple expansion methods, additional chemotypes can be discovered; 27 thus, we also included compounds that were nearest neighbors based on chemical or biological similarity to the RNA binders. Comparison of the resulting set of ~3700 compounds, termed the “RNA-Focused Library,” with reference to the initial screening collection using Tanimoto similarity, revealed that our new set included similar compounds (high similarity) as well as distinct chemical moieties (low similarity), the latter largely introduced through biological fingerprint nearest-neighbor expansion and ECFP4 naïve Bayesian model expansion ( Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Another competitive Asc-1 inhibitor is S-Methyl-L-Cys (SMLC). Nevertheless ACPP, LuAE00527 and BMS-466442 block uptake and efflux of d-serine, while SMLC inhibits the uptake, but allows the efflux 8,16,18,19,21,46 . We performed the docking of SMLC at the binding site of our Asc-1 outward-open model.…”
Section: Potential Binding Modes Of Competitive Inhibitorsmentioning
confidence: 99%
“…[18][19][20][21] Furthermore, Kutchukian et al reported a comparison of HTSFPs versus structural descriptors in the exercise of hit expansion during an active iterative screening campaign which lead to the identification of a novel Asc-1 inhibitor. 22 In a more recent article, Cabrera and Petrone, proposed a desirability function for selecting HTS assays with optimal informative content for HTSFP definitions. 23 Even though most HTS data is in the industry, and is not publicly accessible, efforts have also been put into the evaluation of publicly accessible HTSFPs build upon 243 HTS assays (biochemical and cell-based) deposited in PubChem for hit expansion.…”
Section: Introductionmentioning
confidence: 99%